Urgensi Literasi Digital Tengku dalam Membangun Kerukunan Umat Beragama - Ibnu, Muslem (Al-Hikmah Media Dakwah, Komunikasi, Sosial dan Kebudayaan, 2023)
Digital literacy skills are very important today. Someone who has good digital literacy skills is a person who is independent and skilled in finding information, and has the ability to choose the type of information needed and present it effectively. As an opinion leader, Tengku must master digital literacy so that he is not mistaken in conveying messages to his followers. This will help prevent inter-religious conflicts in society and promote inter-religious harmony.